Pre-Service Teachers’ Perception of Digital Literacy - Sudana, Putu Ayu Prabawati; Made Hery Santosa; Ni Made Ratminingsih; Ni Nyoman Padmadewi; Luh Putu Sri Adnyani; Luh Putu Artini (Journal of Education Technology, 2023)
Digital Literacy for teachers, including future teachers is one prominent and influential aspect of living in the 21st century. They need to be digitally literate to be engaged in this digital world and to prepare their students to be digitally literate too. This research aims to assess the level of the pre-service teachers’ digital literacy in one public university in Bali, Indonesia. This study was using a survey study. The participants were involving 158 pre-service teachers. Pre-service teachers are students of teaching training or educational study programs, who are prepared with pedagogical content and skills to prepare them to become teachers. The instrument used in collecting the data was a 5-point-Likert-questionnaire, data triangulation a semi-structured interview with seven pre-service teachers was conducted. The questionnaires were analyzed quantitatively. The study revealed that most of the pre-service teachers reported high levels of literacy in all areas. The results of this study would be beneficial as reflections on the pre-service teachers’ digital literacy as a consideration in the institution’s regular review of the curriculum or training for the pre-service teachers.